Практична підготовка– запорука успіху майбутнього фахівця - Діордієв, Володимир Трифонович; Диордиев, Владимир Трифонович; Diordiiev, Volodymyr; Дубініна, Світлана Вікторівна; Дибинина, Светлана Викторовна; Dubinina, Svitlana (Мелітополь: ТДАТУ, 2019)
UK: Розглянуто проблему практичної підготовки фахівців у закладах вищої освіти для набуття ними необхідних компетентностей для майбутньої професійної діяльності. Приділено увагу взаємодії підприємств і університету, спрямовану на удосконалення освітніх програм для підвищення якості практичної підготовки інженерних кадрів. EN: The problem of practical training of specialists in higher education institutions for obtaining the necessary competencies for future professional activity is considered. The attention was paid to the interaction between enterprises and the university, aimed at improving educational programs for improving the quality of practical training of engineers
Practical training is a condition for the success of the future specialist
Keywords: практичне навчання; виробнича практика; професійна діяльність; дуальне навчання; practical training; industrial practice; professional activity; dual education